PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA ANGGOTA POLRI SUBDIT POTDIRGA PADA DITPOLUDARA KORPOLAIRUD BAHARKAM POLRI - Moh. Bonnario; Samsul Fitri (Sekolah Tinggi Manajemen IMMI, 2018)
The research entitled “The Influence of Organizational Motivation and Culture on the Performance of Police Members in the Subdistrict of Potdirga Ditpolairud Baharkam Polri” aims to get an idea of the influence or contribution of motivation and organizational culture in realizing Member performance. This research was conducted using primary data and secondary data from the Subdit Potdirga Ditpolairud Baharkam PolriThe results of the study show that both partially and jointly the motives and organizational culture contribute quite well in realizing the performance of Members. Although the perspective of seeing Members as human capital still needs to be improved, it is not only seen from their involvement in work. Likewise Islamic values in work are solutions that must be continuously instilled.